PALB2 variants in hereditary and unselected Finnish Prostate cancer cases - Pakkanen, Sanna (BioMed Central, 2009)
BACKGROUND: PALB2 1592delT mutation is associated with increased breast cancer and suggestive prostate cancer (PRCA) risk in Finland. In this study we wanted to assess if any other PALB2 variants associate to increased PRCA risk and clinically describe patients with formerly found PALB2 1592delT mutation. METHODS: Finnish families with two or more PRCA cases (n = 178) and unselected cases (n = 285) with complete clinical data were initially screened for variants in the coding region and splice sites of PALB2. Potentially interesting variants were verified in additional set of unselected cases (n = 463). RESULTS: From our clinically defined sample set we identified total of six variants in PALB2. No novel variants among Finnish PRCA cases were found. Clinical characteristics of the variant carriers, including the previously described family carrying PALB2 1592delT, revealed a trend towards aggressive disease, which also applied to a few non-familial cases. Hypersensitivity to mitomycin C (MMC) of lymphoblasts from individuals from the family with 1592delT revealed haploinsufficiency among carriers with altered genotype. CONCLUSIONS: Though any of the detected PALB2 variants do not associate to PRCA in population level in Finland it cannot be ruled out that some of these variants contribute to cancer susceptibility at individual level.